PENGARUH KEPEMILIKAN MANAGERIAL, DEBT COVENANT, LITIGATION, TAX AND POLITICAL COSTS DAN KESEMPATAN BERTUMBUH TERHADAP KONSERVATISMA AKUNTANSI - Shella Deslatu; Yulius Kurnia Susanto (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2010)
Accounting conservatism is defined as managerial accounting choices of accounting methods and estimates within Generally Accepted Accounting Principles (GAAP) that result in the persistent understatement of cumulative reported earnings and net assets over period of time. The objective of the research is to analyze the influence of managerial ownership, debt covenant, litigation, tax and political costs, and growth opportunities on accounting conservatism. The research consists of 22 manufacturing companies listing on Indonesia Stock Exchange. The research using purposive sampling method whereas the criteria are manufacturing companies which are consistently listing on Indonesia Stock Exchange and using a accounting conservatism during period 2005 until 2008. Multiple regression is used to analyze the data. The results of the research showed that litigation had significant effect to accounting conservatism. Managerial ownership, debt covenant, tax and political costs and growth opportunities had not significant effect to accounting conservatism in manufacturing companies.